Prevalence and impact on quality of life of dermatological disorders and their associated factors among the elderly in urban areas of Dar es Salaam, Tanzania - Uwesu Muki; Grace Shayo; Eliaichi Minja; Muhammad Bakari; Ashura Kazema; Salum J. Lidenge (Scientific Reports)
Abstract The global population of people aged 60 years or older (elderly) is increasing. Skin disorders are reported to be common in this population. In view of limited data available, this study determined the burden, pattern and impact on quality of life (QoL) of dermatological disorders among the elderly in Tanzania. This was a community-based cross-sectional study conducted from August to November 2021 in Ilala Municipality, Dar es Salaam. Participants were obtained through simple random sampling in multiple stages. Diagnoses were made through a clinical assessment initially performed by a dedicated dermato-venereology officer, and confirmed by a Dermatologist using digital photographs. Quality of Life was assessed using a validated Dermatology Quality of Life Index (DLQI) with scores ranging from 1 to 30. The wealth index was graded from class 1 (poor) to class 5 (rich). Data were analyzed through Chi-squared test, Poisson Logistic regression, and analysis of variance. A total of 694 elderlies were enrolled. The overall prevalence of dermatological disorders was 85.5% (593). The most frequent category of dermatological disorders were skin infections and infestations (36.1%); eczemas (34.7%); papulosquamous eruptions (6.5%), and keratinization disorders (2.6%). Autoimmune disorders comprised 1.4%, while vascular disorders and tumors comprised 1.2% of all cases. A small proportion (1.7%) of the elderlies had ≥ 2 skin disorders. In multivariate analysis the wealth index was found to be associated with the presence of the dermatological disorder. There was a 61% impairment in QoL due to the dermatological disorders. Dermatological disorders among the elderly were common and were associated with the wealth index. They had a significant impact on quality of life. Appropriate control measures to address dermatological disorders among the elderly are needed.